Study of Magnesium, Potassium and Ferritin Levels in the Blood Serum of People Infected with COVID-19 - Rafal Ahmed Lilo; Zahraa M. Al-Taee; Liqaa Y. Mohsen; Zeena Hadi Obaid Alwan; Mustafa Abdulrahman A. Al-Kinani (Medical Journal of Babylon, 2025)
Background: The WHO has declared Coronavirus disease COVID-19 as a worldwide pandemic for the first few months of 2020. Inadequate immunity may result from the immune system’s ability to function poorly due to a lack of vitamins and minerals in plasma. Objective: This research aimed to evaluate the circulating potassium, magnesium, and ferritin concentrations and their potential to use as a marker in COVID-19 infection. Materials and Methods: The study’s subjects were split into five age groups based on their respective levels of infection with the coronavirus (P ~ 0.05), circulating potassium, magnesium, and ferritin concentrations were measured in the blood serum via the Bioassay Technology laboratory techniques. Results: Significant (P ˂ 0.05) variations were identified in the previous circulating elements: 25% of patients have low potassium, equally distributed among boys and females. 19% of patients have high potassium levels, particularly in males; In terms of magnesium, the proportion of patients with a high concentration was 58% (males had a greater percentage than females), whereas the reduction was only in 3%; Ferritin was below normal are found in just 3% of patients, and there has been no discernible increase in ferritin levels. Conclusions: Due to the nature of everyday jobs, the young and middle-aged populations are the most susceptible to contracting the coronavirus. Hypermagnesemia is a significant indicator of the severity of a viral infection. While COVID-19 patients frequently have hypokalemia as an electrolyte imbalance. It is possible to depend on the ferritin level as a gauge of the infection’s severity.